Mobile underwater in situ gamma-ray spectroscopy to localize groundwater emanation from pockmarks in the Eckernförde bay, Germany. (October 2018) - Patiris, Dionisis L.; Tsabaris, Christos; Schmidt, Mark; Karageorgis, Aristomenis P.; Prospathopoulos, Aristides M.; Alexakis, Stylianos; Linke, Peter
Abstract: Eckernförde Bay in the Baltic Sea is well-known for the pockmarks areas which are located in the centre and off the southern shore-line of the bay emanating groundwater in a non-continuous but episodic way. Mobile underwater in situ gamma-ray spectroscopy is exploited proving that both 214 Bi and 40 K are efficient radiotracers for localization of seepage areas whenever either sediment is in mixture with the emanating fluid or resuspension of surface sediment occurs as a side effect of the fluid emanation. Highlights: Application of mobile underwater in situ gamma-ray spectroscopy. Localization of pockmarks emanating groundwater. Radon progeny 214 Bi proved an efficient radiotracer for localization purposes. Potassium 40 K is suggested as additional to radon radiotracers to localize fluid emanation areas whenever sediment is in mixture with the fluid or resuspension of sediment occurs.